(untitled) (Research, Society and Development, 2020)
This article promotes a state-of-the-art research on the theme of Professional and Technological Education based on the dissertations developed by the first class of the Strictu Sensu Graduate Program in Professional and Technological Education at IFCE - ProfEPT, describes dissertation defenses that were made in 2019. As an objective is the mapping of academic production in a way that realizes the extent to which the works share among themselves the central axis of the Program, namely, Professional and Technological Education. To this end, a survey was carried out of the keywords that are linked to Technological Education in academic production, so that it can be mapped as interdisciplinarities that are manifested in the 24 dissertations raised. As for the methodology, the approach is qualitative and classified as exploratory bibliographic. In addition, it will be possible, based on the effort undertaken, to identify how the theoretical field has evolved in the context of the program, as well as possible gaps that exist, so that it may give rise to new studies of upcoming classes, whether to deepen a theme or to undertaking studies with a higher degree of novelty. In the analysis of data were developed that allow the identification through the keywords of the theoretical fields in the researches carried out, thus concluding that there is a convergence of the dissertations with the Professional and Technological Education, evidencing, therefore, an enlarged vision of the whole spectrum contemplated in the ProfEPT dissertations.